When Long-Lasting Food Selectivity Leads to an Unusual Genetic Diagnosis: A Case Report. - Da Lozzo, Prisca; Magnolato, Andrea; Del Rizzo, Irene; Sirchia, Fabio; Bruno, Irene; Barbi, Egidio (J Adolesc Health, 2019)
Hereditary fructose intolerance is an autosomal recessive disorder of fructose metabolism caused by catalytic deficiency of aldolase B enzyme [1]. The disease is typically expressed when fructose- and sucrose-containing foods are first introduced in the diet; acute manifestations include nausea, vomiting, abdominal distress, and symptomatic hypoglycemia [1,2]. Chronic fructose ingestion eventually leads to poor feeding, growth retardation and gradual liver and/or renal failure [3,4]. Some patients may remain undiagnosed until adulthood because of a self-protective avoidance of sweet tasting food that prevents the development of acute toxicity from fructose containing food; however, these subjects may suffer intermittent symptoms throughout life, leading to potentially serious misdiagnosis [4]. We report the case of a patient with unrecognized hereditary fructose intolerance in which chronic gastrointestinal complaints, low body weight, and unexplained food avoidance were addressed as manifestations of an eating disorder during adolescence.

What is known about deferasirox chelation therapy in pediatric HSCT recipients: two case reports of metabolic acidosis. - Fucile, Carmen; Mattioli, Francesca; Marini, Valeria; Gregori, Massimo; Sonzogni, Aurelio; Martelli, Antonietta; Maximova, Natalia (Ther Clin Risk Manag, 2018)
To date, in pediatric field, various hematological malignancies are increasingly treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT). Iron overload and systemic siderosis often occur in this particular cohort of patients and are associated with poor prognosis. We describe herein the case of two allo-HSCT patients, on treatment with deferasirox; they showed histopathological elements compatible with venoocclusive disease or vanishing bile duct syndrome in ductopenic evolution before deferasirox started. The first patient developed drug-induced liver damage with metabolic acidosis and the second one a liver impairment with Fanconi syndrome. After withdrawing deferasirox treatment, both patients showed improvement. Measurements of drug plasma concentrations were performed by HPLC assay. The reduction and consequent disappearance of symptoms after the suspension of deferasirox substantiate its role in inducing hepatic damage, probably enabling the diagnosis of drug-induced liver damage. But the difficulties in diagnosing drug-related toxicity must be underlined, especially in compromised subjects. For these reasons, in patients requiring iron-chelating therapy, close and careful drug therapeutic monitoring is strongly recommended.

What is the quality of the maternal near-miss case reviews in WHO European Region? Cross-sectional study in Armenia, Georgia, Latvia, Republic of Moldova and Uzbekistan. - Bacci, Alberta; Hodorogea, Stelian; Khachatryan, Henrik; Babojonova, Shohida; Irsa, Signe; Jansone, Maira; Dondiuc, Iurie; Matarazde, George; Lazdane, Gunta; Lazzerini, Marzia (BMJ Open, 2018)
OBJECTIVES: The maternal near-miss case review (NMCR) cycle is a type of clinical audit aiming at improving quality of maternal healthcare by discussing near-miss cases. In several countries this approach has been introduced and supported by WHO and partners since 2004, but information on the quality of its implementation is missing. This study aimed at evaluating the quality of the NMCR implementation in selected countries within WHO European Region. DESIGN: Cross-sectional study. SETTINGS: Twenty-three maternity units in Armenia, Georgia, Latvia, Moldova and Uzbekistan. ASSESSMENT TOOLS: A predefined checklist including 50 items, according to WHO methodology. Quality in the NMCR implementation was defined by summary scores ranging from 0 (totally inappropriate) to 3 (appropriate). RESULTS: Quality of the NMCR implementation was heterogeneous among different countries, and within the same country. Overall, the first part of the audit cycle (from case identification to case analysis) was fairly well performed (mean score 2.00, 95% CI 1.94 to 2.06), with the exception of the 'inclusion of users' views' (mean score 0.66, 95% CI 0.11 to 1.22), while the second part (developing recommendations, implementing them and ensuring quality) was poorly performed (mean score 0.66, 95% CI 0.11 to 1.22). Each country had at least one champion facility, where quality of the NMCR cycle was acceptable. Quality of the implementation was not associated with its duration. Gaps in implementation were of technical, organisational and attitudinal nature. CONCLUSIONS: Ensuring quality in the NMCR may be difficult but achievable. The high heterogeneity in results within the same country suggests that quality of the NMCR implementation depends, to a large extent, from hospital factors, including staff's commitment, managerial support and local coordination. Efforts should be put in preventing and mitigating common barriers that hamper successful NMCR implementation.
Keywords: Armenia; Checklist; Cross-Sectional Studies; Female; Georgia; Humans; Latvia; Maternal Mortality; Medical Audit; Moldova; Near Miss, Healthcare; Pregnancy; Pregnancy Complications; Quality Improvement; Uzbekistan

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Withdrawal Assessment Tool-1 Monitoring in PICU: A Multicenter Study on Iatrogenic Withdrawal Syndrome. - Amigoni, Angela; Mondardini, Maria Cristina; Vittadello, Ilaria; Zaglia, Federico; Rossetti, Emanuele; Vitale, Francesca; Ferrario, Stefania; Savron, Fabio; Coffaro, Giancarlo; Brugnaro, Luca; Amato, Roberta; Wolfler, Andrea; et al. (Pediatr Crit Care Med, 2017)
OBJECTIVES: Withdrawal syndrome is an adverse reaction of analgesic and sedative therapy, with a reported occurrence rate between 17% and 57% in critically ill children. Although some factors related to the development of withdrawal syndrome have been identified, there is weak evidence for the effectiveness of preventive and therapeutic strategies. The main aim of this study was to evaluate the frequency of withdrawal syndrome in Italian PICUs, using a validated instrument. We also analyzed differences in patient characteristics, analgesic and sedative treatment, and patients' outcome between patients with and without withdrawal syndrome. DESIGN: Observational multicenter prospective study. SETTING: Eight Italian PICUs belonging to the national PICU network Italian PICU network. PATIENTS: One hundred thirteen patients, less than 18 years old, mechanically ventilated and treated with analgesic and sedative therapy for five or more days. They were admitted in PICU from November 2012 to May 2014. INTERVENTIONS: Symptoms of withdrawal syndrome were monitored with Withdrawal Assessment Tool-1 scale. MEASUREMENTS AND MAIN RESULTS: The occurrence rate of withdrawal syndrome was 64.6%. The following variables were significantly different between the patients who developed withdrawal syndrome and those who did not: type, duration, and cumulative dose of analgesic therapy; duration and cumulative dose of sedative therapy; clinical team judgment about analgesia and sedation's difficulty; and duration of analgesic weaning, mechanical ventilation, and PICU stay. Multivariate logistic regression analysis revealed that patients receiving morphine as their primary analgesic were 83% less likely to develop withdrawal syndrome than those receiving fentanyl or remifentanil. CONCLUSIONS: Withdrawal syndrome was frequent in PICU patients, and patients with withdrawal syndrome had prolonged hospital treatment. We suggest adopting the lowest effective dose of analgesic and sedative drugs and frequent reevaluation of the need for continued use. Further studies are necessary to define common preventive and therapeutic strategies.
Keywords: Adolescent; Analgesics; Child; Child, Preschool; Critical Care; Female; Humans; Hypnotics and Sedatives; Iatrogenic Disease; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Italy; Logistic Models; Male; Prospective Studies; Respiration, Artificial; Substance Withdrawal Syndrome

When a lymphatic malformation determines a bowel volvulus: Are clinical status and images always reliable? - Guida, Edoardo; Di Grazia, Massimo; Cattaruzzi, Elisabetta; Bussani, Rossana; Rigamonti, Waifro; Lembo, Maria Antonietta (Int J Surg Case Rep, 2016)
INTRODUCTION: An acute abdomen in the form of small-bowel volvulus could be a presentation of a lymphatic malformation in childhood. CASE PRESENTATION: A 5year old male was admitted to our Institute for an acute abdomen. Clinical aspects and radiological images were not specific for a certain diagnosis. Laparotomy revealed a big soft mass, with a milky content, completely involving about 50cm of ileus with a partial volvulus of the intestinal loop. A complete mass excision and also a bowel involved resection were performed. After a histological examination, a lymphatic malformation was diagnosed. DISCUSSION: The diagnosis of a mesenteric lymphatic malformation could be intraoperative and a complete resection should be the treatment of choice. Sometimes it could be necessary to perform an involved bowel tract resection in the case of volvolus with ischemia. CONCLUSIONS: Paediatricians and surgeons should bare in mind that an intrabdominal lymphatic malformation may present as a nonspecific an acute abdomen caused by a bowel volvolus and diagnosis may not be so simple preoperatively.

Wharton's jelly derived mesenchymal stromal cells: Biological properties, induction of neuronal phenotype and current applications in neurodegeneration research. - Frausin, Stefano; Viventi, Serena; Verga Falzacappa, Lucia; Quattromani, Miriana Jlenia; Leanza, Giampiero; Tommasini, Alberto; Valencic, Erica (Acta Histochem, 2015)
Multipotent mesenchymal stromal cells, also known as mesenchymal stem cells (MSC), can be isolated from bone marrow or other tissues, including fat, muscle and umbilical cord. It has been shown that MSC behave in vitro as stem cells: they self-renew and are able to differentiate into mature cells typical of several mesenchymal tissues. Moreover, the differentiation toward non-mesenchymal cell lineages (e.g. neurons) has been reported as well. The clinical relevance of these cells is mainly related to their ability to spontaneously migrate to the site of inflammation/damage, to their safety profile thanks to their low immunogenicity and to their immunomodulation capacities. To date, MSCs isolated from the post-natal bone marrow have represented the most extensively studied population of adult MSCs, in view of their possible use in various therapeutical applications. However, the bone marrow-derived MSCs exhibit a series of limitations, mainly related to their problematic isolation, culturing and use. In recent years, umbilical cord (UC) matrix (i.e. Wharton's jelly, WJ) stromal cells have therefore emerged as a more suitable alternative source of MSCs, thanks to their primitive nature and the easy isolation without relevant ethical concerns. This review seeks to provide an overview of the main biological properties of WJ-derived MSCs. Moreover, the potential application of these cells for the treatment of some known dysfunctions in the central and peripheral nervous system will also be discussed.

When Feeding Difficulties Are due to Genetics: The Case of Familial Partial 9q Duplication. - Travan, Laura; Rocca, Maria Santa; Buonomo, Francesca; Cleva, Lisa; Pecile, Vanna; De Cunto, Angela (J Investig Med High Impact Case Rep, 2015)
Chromosomal abnormalities may cause growth failure before or since birth. 9q duplication is reported as a cause of intrauterine growth restriction, mild dysmporphism, and intellectual disabilities. We report a case of a maternally inherited 9q21.31q21.33 duplication causing prenatal and postnatal growth restriction with feeding refusal and mild facial dysmorphisms, prenatally diagnosed by single-nucleotide polymorphism array analysis. Hypothesis of the possible pathogenic mechanisms are discussed.

When does postnatal catch-up fat occur in late preterm infants? - De Cunto, Angela; Paviotti, Giulia; Demarini, Sergio (Acta Paediatr, 2014)
Keywords: Body Composition; Humans; Infant, Premature

A web-based system for total parenteral nutrition prescription in a pediatric hospital - biomed 2010. - Bava, Michele; Bradashia, Fulvio; Rovere, Francesca; Maestro, Alessandra; Vecchi Brumatti, Liz; Accardo, Agostino; Paparazzo, Rossella; Zanon, Davide (Biomed Sci Instrum, 2010)
otal Parenteral Nutrition (TPN) is defined as feeding a patient by infusing nutrients intravenously, bypassing the usual process of eating and digestion. There are two kinds of TPN: short-term TPN may be used when a patient's digestive system is temporarily nonfunctional because of an interruption in its continuity; long-term TPN is used to treat patients with an impairment or a lack in nutrient absorption. TPN has extended the life of children born with nonexistent or severely deformed digestive organs and is a vital support for these patients. In Burlos Pediatric Department, pediatricians fill in a pharmacy request form in which nutritional needs are included for each patient. Subsequently, clinical pharmacists evaluate the patients individual data and decide which TPN formula to prepare. To enhance the TPN prescription process, an intranet web-based system has been developed to replicate the original paper-based forms. The software, developed in PHP and based on open source tools and services, has been constructed according to pharmacists requirements. These professionals, together with the Hospital Information System technicians, thanks to the availability of affordable instruments, perceive the advantages that such a system would have in improving clinical practice and quality of care. The system was devised with the goal to avoid common reading errors, to improve the correct text comprehension, to ensure prescription preparation, administration and tracking. According to a process of total quality control, the system reduces clinical risks regarding issues such as the correct and rapid availability of medical prescriptions and the incorrect identification of the patients. In comparison with paper-based TPN prescriptions, electronic-based forms have reduced the incidence of errors, the possible lack of patient data and reading misunderstandings. Regarding future improvements, IT technicians are defining the procedures to implement digital signature and medical aspects of the electronic TPN medical prescriptions.

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal